2021
DOI: 10.11648/j.jeece.20210601.14
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic and Dilute Acid Hydrolyses of Maize Stalk Substrate in Bio-ethanol Production

Abstract: Biofuels have been identified as suitable in combating climate change as a result of green gas emissions from fossil fuels. Bioethanol is a biofuel from lignocellulosic biomass is considered a viable renewable energy alternative to fossil fuels. However, the recalcitrance of biomass feedstocks due to the presence of lignin, creates a barrier to glucose fermentation. This study compares enzymatic and dilute acid hydrolyses of cellulose substrates obtained from pretreated maize stalk. The cellulose substrates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…6 showed that highest concentration of sugars (1.07 mg/ mL) was produced from the rice chaff, followed by yam peel which produced 0.87 mg/mL while groundnut shell produced lowest sugar concentration of 0.75 mg/mL. Kolajo [39] mentioned in her report that cellulase enzymes yielded more (4.04 mg/mL) fermentable sugars than dilute acid or alkali that produced 3.76 mg/mL. This reaffirms the report being presented that crude cellulase produced by Aspergillus niger S48 hydrolyzed pre-treated lignocellulosic agricultural biomass to fermentable sugars.…”
Section: Pre-treatment and Saccharification Of Plant Wastes To Hydrolysable Sugarsmentioning
confidence: 95%
“…6 showed that highest concentration of sugars (1.07 mg/ mL) was produced from the rice chaff, followed by yam peel which produced 0.87 mg/mL while groundnut shell produced lowest sugar concentration of 0.75 mg/mL. Kolajo [39] mentioned in her report that cellulase enzymes yielded more (4.04 mg/mL) fermentable sugars than dilute acid or alkali that produced 3.76 mg/mL. This reaffirms the report being presented that crude cellulase produced by Aspergillus niger S48 hydrolyzed pre-treated lignocellulosic agricultural biomass to fermentable sugars.…”
Section: Pre-treatment and Saccharification Of Plant Wastes To Hydrolysable Sugarsmentioning
confidence: 95%
“…Fossil fuels are still the primary source of energy used commercially. The massive use of these fos-and plant waste, such as lignocellulose plants [2][3][4][5][6][7][8][9]. Low toxicity, fewer emissions, and biodegradability are bioethanol advantages compared to fossil fuels.…”
Section: Introductionmentioning
confidence: 99%